Pre-Service EFL Students’ Perceptions of Scripted vs. Improvisational Drama Play in Enhancing Spontaneous Speaking Fluency - Achmad Nabel Rahmattullah; A.K. Amarullah; Syamdianita, Syamdianita; Sjamsir, Hasbi (Borneo Educational Journal (Borju), 2025)
This study explored the perceptions of pre-service EFL students regarding the role of drama play in enhancing their speaking fluency. Speaking fluency is a critical skill for Indonesian EFL learners, particularly for those preparing to be educators. Despite the integration of drama-based learning in language education many existing methods focus on memorization and scripted dialogues, which may not adequately foster spontaneous speaking skills. This study uses a qualitative phenomenological approach and collects data using semi-structured interviews and journals from pre-service teachers in Samarinda. The study found that drama play significantly enhanced students’ confidence, vocabulary, and pronunciation. However, while scripted drama enhances structured speech fluency, they did not significantly improve students' ability to engage in spontaneous conversations. In contrast, improvisational elements of drama play were perceived as more effective in promoting real-time communicative competence. This study highlights the need for a balanced approach that integrates both scripted and unscripted drama techniques to optimize speaking fluency in EFL education. These findings provide valuable insights for educators and curriculum developers focused on developing strategies to improve learners’ communicative skills in English.